Reconsidering Land System Changes in Borderlands: Insights from the China-ASEAN Borderland - Hua, Xiaobo; Kono, Yasuyuki (Problemy Ekorozwoju, 2020)
This study contributes to the literature on how to explicitly describe, track, and interpret the structure and dynamics of land systems in borderlands. The shift in land system science analytics from place-based toward larger-scale analysis of interactions and connections in a globalized context provides an opportunity to synthesize the knowledge about borderlands. This paper argues that studies on land system changes in borderlands need to thoroughly link the features of borderland regions with multiple interactions – on either or both sides of a border – rather than simply focusing on shifts within closed national boundaries. Furthermore, this paper provides important insights that can advance existing approaches to track and interpret changes in the land systems of borderlands.